Social network analysis of heterogeneous subjects driving spatial commercialization of traditional villages: A case study of Tanka Fishing Village in Lingshui Li Autonomous county, China - Cheng, Yeqing; Fei, Xueyan; Luo, Liusha; Kong, Xiping; Zhang, Jinping (Habitat international, 2025)
Rural spatial commercialization has emerged as a focal point of interest in the field of rural geography. This study, Taking Tanka Fishing Village of Xincun Town in Lingshui Autonomous County of Hainan Province as a case, and based on the data and materials collected from field investigation and semi-structured questionnaire interview, analyzed the evolution process and characteristics of spatial commercialization, and examined the social network relationships and its underlying mechanism driven by multiple heterogeneous subjects utilizing Social Network Analysis. The aim is to provide practical guidance for the industrial transformation, upgrading, and preservation utilization of Tanka Fishing Village, as well as other traditional villages with similar profiles. The findings indicate that, firstly, as rural spaces transition from productivism to post-productivism and multi-functional countryside, the spatial commercialization of Tanka Fishing Village has also undergone a transformation from being predominantly fisheries to a fusion of fisheries and tourism, and subsequently to an integration of fisheries, tourism and culture. Secondly, the evolution of spatial commercialization within Tanka Fishing Village is a practical process where various heterogeneous subjects, including governments, businesses, village committees, Tanka people, and tourists, establish social relationship networks through a series of negotiations and strategic interactions. The social network relationship of heterogeneous subjects has gradually shifted from an ‘enterprise-driven cluster network’ to a ‘government-led tight network’ and ultimately to a ‘relatively balanced network driven by rural talents’. The role of external heterogeneous subjects, such as enterprises and government departments, in the social networks has progressively weakened, whereas the importance of internal heterogeneous subjects, including social groups and rural talents, has correspondingly increased. This shift has fortified the endogenous momentum of spatial commercialization in Tanka Fishing Village. Ultimately, strengthening government policy guidance, fostering innovative business models, encouraging villager participation, and refining the benefit-sharing mechanism are crucial strategies for promoting the sustainable commercial development and preservation of Tanka Fishing Village in Lingshui Autonomous County, China.